EFFECT OF LEAD ACETATE TOXICITY ON THE HISTOLOGICAL AND BIOCHEMICAL CHANGES IN LIVER AND KIDNEY OF FISH ROHU (LABEO ROHITA) - ALI, I; ZULQARNAIN, S; RASHEED, S; HUSSAIN, A; SAEED, I (Biological and Clinical Sciences Research Journal, 2024)
The objective of this study was to investigate the histological alterations in the kidneys and liver of the fish known as Rohu (Labeo rohita). For seven days, 100 L. rohita fingerlings were kept in a glass aquarium to acclimate. The fingerlings were split into four groups, with 25 fingerlings in each group. Lead acetate was created in four concentrations: Nil; 1/5th LC50 (6.86 ppm); 1/10th LC50 (3.43 ppm); and 1/20th LC50 of 1.71 ppm. These concentrations were then randomly assigned to 4 groups: 1; (control); 2; 3 and 4 in that order. After 10, 20, 30, and 40-days fillets were dissected and the Liver and kidney were separated for histopathology analysis. The major histopathological changes observed in the liver were melano-macrophage canters, leukocyte infiltration, cytoplasmic degeneration, and pyknosis, while the changes in the kidney were renal tubule atrophy, aggregation of inflammatory cells, loss of cellular integrity, renal tubule degeneration, uneven renal tubule diameters, and few necrotic regions. The fingerlings in G-2, which received a higher dose of lead acetate during the fourth week of the research, had the most lesions. As the concentration of lead acetate dropped during this time, as it did in the fingerlings of G-3 and G-4, fewer lesions were observed in the liver and kidneys. However, compared to the fourth week of the trial, fewer lesions were seen in the kidneys and liver in the first, second, and third weeks. The fingerlings' protein and moisture contents demonstrated a declining tendency as compared to the group-1 (control) (1.75 vs. 2.20), and the differences in the protein contents were not statistically significant (P<0.05). In a similar vein, the liver and kidneys' moisture contents trended downward when compared to the control group. Overall, the study's findings showed that greater concentrations of lead acetate had a negative impact on the kidneys and liver of the fish Rohu; as a result, it is important to limit fish exposure to this chemical in order to maintain the fishes' overall health.